KEBIJAKAN PERANCIS MENGUSIR ETNIS ROMA PADA MASA PEMERINTAHAN NICOLAS SARKOZY TAHUN 2010 - Zepry "; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research will examine the background of what Nicolas Sarkozy as president of France in a phenomenal policy to extrude the ethnic Roma from France. Ethnic Roma are the largest ethnic minority in Europe who can move residence from one region to another. However, this activity is not ethnic Roma were warmly welcomed by other European countries so Ethnic Roma often get discrimination from their state residence. The purpose of this study is to find out who is Ethnic Roma and discrimination obtained by them, and knows how the state of immigration in France and Nicolas Sarkozy in his policy to extrude the Ethnic Roma from France in 2010.The research was conducted using research methods literature where the data and information obtained from sources which are relevant to the research problems. This reasearch uses perspective to analyze individual behavioralisme of Nicolas Sarkozy and Human Security theory proposed by Barry Buzan, and the concept of national interest of Jack C. Plano and Roy Olton.This research shows that the Ethnic Roma who came from India's Punjab have experienced discrimination since they migrated to Europe from the famine that hit them. Nicolas Sarkozy issued a phenomenal policy to extrude the ethnic Roma from France because the French politician Nicolas Sarkozy is coming from immigrant families who are representative of the Hungarian right-wing politics in France who hated immigrants in France.Keywords: Ethnic Roma, Immigration, Nicolas Sarkozy, Discrimination